STAGES AND ERROR ANALYSIS IN QUESTION FORMATION OF FIVE GRADER STUDENTS - Matiini, Gharizi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2019)
The present study aims to seek the stages of how young learners forming their questions. It is believed that in making the questions, learners are going trough several developments until they can create the question perfectly. Stages from Pienemann, Johnston & Brindley (1988) were used as the developmental classification of question formation. While Richards’ (1973) Errors stages were used in analyzing the errors of question formation. Two students with different genders were taken as the participants with narration manuscripts as the data collection. The results were very surprising; both learners could perform complex question formations with only few errors. Though they are young learners, structuring a complex question seemed not difficult for them. However, the more difficult the question formats, the more errors the students made. They students commonly simplified the questions format, which made the formats sometimes, went wrong. From this interesting result, It is expected that this study can be an initial effort to conduct bigger and wider area of research in the future.